Curriculum Foundations for Arabic Language Education in the AI Era: Holistic, Juridical, and Technological Perspectives - Nugraha, Adhia; Syafe'i, Isop (Institut Agama Islam Negeri Palangka Raya, 2025)
Arabic Language Education (ALE) in Indonesia faces a persistent gap between curricular goals and actual learner proficiency, exacerbated by limited integration of artificial intelligence (AI) in instruction. This study investigates how AI can transform ALE in Indonesia by aligning technological innovation with cultural and spiritual values. Employing a qualitative exploratory design, the research integrates documentary analysis, meta-synthesis, and comparative case studies from Malaysia, the UAE, and Saudi Arabia three nations leading in AI adoption for Arabic instruction. It also draws empirical data from an AI-assisted pilot project at Fatimah Azzahro Islamic Boarding School, West Java. Results reveal that intelligent tutoring systems, personalized learning platforms, and spiritually embedded AI tools significantly enhance engagement, retention, and contextual understanding. The Indonesian pilot recorded a 77% rise in student engagement and 67% in long-term retention, demonstrating the effectiveness of culturally responsive AI integration. Comparative insights highlight the need for a hybrid paradigm combining AI with value-based education rooted in national ideology and Qur’anic ethics. The study advocates for a holistic ALE framework that bridges philosophical ideals with scalable, technology-driven solutions. This model positions Indonesia to develop an ALE system that is globally competitive, spiritually grounded, and responsive to the demands of Society 5.0.